Pengembangan Desa Batuan Sebagai Desa Wisata Berbasis Edukasi Melalui Pelatihan Pengemasan dan Pemasaran Paket Wisata Berlandaskan Tri Hita Karana - Ni Made Ayu Natih Widhiarini; Anak Agung Istri Putera Widiastiti; Kadek Ayu Ekasani; I Gusti Ayu Suwintari; Ida Ayu Adriana Nareswari (Lembaga Pengembangan Kinerja Dosen, 2025)
Batuan Tourism Village is located in the Sukawati District, Gianyar Regency, Bali, and has several potentials in terms of historical, cultural, customary, as well as tourism products, both goods and services. The presence of Pura Puseh in Batuan Village is the starting point of tourist attraction in Batuan Tourism Village. However, despite its popularity as a culturally-based tourism village, the percentage of length of stay and time of spend of tourists in Batuan Tourism Village is still very low. This results in minimal tourism activities occurring in Batuan Tourism Village. The lack of information about Batuan Tourism Village accessible to tourists and the absence of Local Tour Guides assigned to tourism spots in Batuan Tourism Village. Therefore, this study aims to develop Batuan Village into an educational tourism village through the role of Local Champions and implementing the concept of Tri Hita Karana using several methods, namely educational methods, persuasive methods, and technology transfer methods. Through the implementation of activities with these methods, the P2MD Batuan Village group produces: (1) the role of local champions as local tour guides, (2) the formation of integrated tour packages, (3) establishing cooperation partnerships with travel agents, (4) the existence of handbooks in physical and digital forms accessible through barcode scanning, and (5) the existence of promotional videos aimed at facilitating tourists to learn about Batuan Tourism Village.